LncRNA PVT1 regulates VEGFC through inhibiting miR‐128 in bladder cancer cells. Issue 2 (4th August 2018) - Yu, Cui; Longfei, Liu; Long, Wang; Feng, Zeng; Chen, Jinbo; Chao, Li; Peihua, Liu; Xiongbing, Zu; Hequn, Chen
Abstract : Long noncoding RNA PVT1 is considered to be an oncogene in multiple cancers. Our previous studies indicated that PVT1 levels were higher in bladder cancer tissue and correlated with clinical progression and poor prognosis in bladder cancer patients. A bioinformatics analysis showed that PVT1 may regulate VEGFC expression through miR‐128 as a competing endogenous RNA (ceRNA). In this study, we demonstrated that PVT1 expression levels affect the proliferation and migration ability of bladder cancer cells. Moreover, PVT1 knockdown significantly decreased the proliferation capacity of bladder cancer cells in nude mice. Luciferase assays and RNA‐binding protein immunoprecipitation were performed to investigate the potential mechanism of ceRNAs in the regulation of PVT1 and VEGFC. The results showed that the increased number of PVT1 transcripts interacted directly with miR‐128 to decrease miR‐128 binding to the VEGFC 3′‐untranslated region. This effect suppressed VEGFC mRNA degradation by miR‐128. In conclusion, these results indicated that PVT1 might play a critical role in bladder cancer tumorigenesis via miR‐218 and VEGFC. Therefore, PVT1 could be a new biomarker for bladder cancer diagnosis and therapy. Abstract : PVT1 might play a critical role in bladder cancer tumorigenesis via miR‐218 and VEGFC. PVT1 could be a new biomarker for bladder cancer diagnosis and therapy.